A study of public’s perception on the design for bus stops / Nur Amirah Mohd Yusop - Mohd Yusop, Nur Amirah (Faculty of Architecture, Planning and Surveying, 2013)
In order to achieve the high-quality public infrastructure, the local authority needs to be coordinated with efficient and reliable services in their public facilities management. The aimed of research is to study the public’s perception on the design for bus stop in Malaysia and focused on the provision of safe, comfortable, and convenient of bus stop design in Malaysia. Besides that, the concentration will be given on the issue of bus stop comfort and design. In this research, the case studies of bus stop were carried out in Klang Valley. These case studies have various types of bus stops and will be studied on their own building materials and design. The data collection based on two main sources that were primary and secondary data were collected in order to fulfil the research requirement. The objective of this research is to study the existing of standard design guidelines regarding to the bus stops design. In addition, the objective is also to identify the level of satisfaction of the users toward the bus stops design and the impacts of the bus stop design on passenger comfort. The method carried out was through questionnaires and analysis. Then, after the analyses of all the data and information, recommendations are given on favourable design of bus stops that chosen by public. In generally, the consistency for good design and the provision of bus stop amenities, making bus stops easier to identify and better matched to their use and the local authority also should improve and maintain the design guidelines to maximize the effectiveness of bus stop design.